Criminal strategies of competing protagonists in the 'development' of Crossroads 1990-9: The Transition from Apartheid "oilspot" to democratic civil society - Greenwell, Anne W (Institute of Criminology, 2016)
The history of Old Crossroads started in 1975 when indigent families from the Eastern Cape, began arriving in search of work in the Cape Town area of the Western Cape. They erected their shack/homes in the bush areas bordering the Nyanga township that is located twenty-two kilometres out of Cape Town near the N2highway and across it the airport. As squatters they struggled for survival and the right to remain, under the leadership of a 'traditional' rural type Headman called Johnson Ngxobongwana, who negotiated on their behalf with the regional and local government authorities. A precarious and volatile balance of power between these and the informal-settlement leadership often resulting in conflict ensued and, it is claimed, had prevented socio-economic development of the area. During a spell in prison on corruption charges Ngxobongwana had been turned from his "struggle" leadership adversary role to be a client/puppet of the apartheid government authorities by cooperating with them in opposing the lNC and its youth structures known as the"comrades". This had resulted in a major outbreak of violence led by his "witdoeke"vigilante group of older local 'traditional' leaders and their followers backed by the local government authorities and supported by government security forces attacking the residents of KTC, burning their homes and laying the area to waste on the pretext of clearing out the "comrades". Since then there has been ongoing low-intensity conflict, criminal activity and intimidation often erupting into sporadic violence in the Old Crossroads urban and informal-settlements. The period of history from 1976-1986 is comprehensively covered by Josette Cole in her book on "Crossroads" (1987). This dissertation will attempt to take up the story from there but the main focus of the research will be on the years between 1990-1999.During this period the writer/researcher has been active, initially as a 'repression' monitor with the Black Sash Monitoring Group until it closed down in 1994, and from 1995-1999, as a 'peace' monitor with UMAC (Urban Monitoring Awareness Committee). Through her involvement with both these Human Rights NGOs (nongovernment organizations) she has been able, most particularly in Old Crossroads, to meet and interact with representatives of the various constituencies there including the security forces and local government authorities. She has kept a journal throughout which has become a Research Diary reflecting the important events, the interpersonal, as well as the more formal group meetings that occurred. It was only in1996 that the possibility of a dissertation took root and she began to conduct more formal semi-structured open-ended interviews with the key role-players which were electronically recorded.